Notes on the History of Scientific Health Societies in Cienfuegos - Víctor René Navarro Machado; Alfredo Darío Espinosa Brito (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2016)
Scientific societies emerged in Cuba in the second half of the nineteenth century as a result of the scientific and technological development, the need to disseminate the best experiences, and certain social, political, and economic circumstances. This paper aims to present the most important events related to the development of scientific health societies in Cienfuegos in chronological order. For this purpose, a historical research was conducted involving an extensive literature review and key informant interviews. During the colonial and republican period, Cienfuegos stood out because of the creation and sustainability of these societies. The first formal attempt of Cuban doctors to work together took place in Cienfuegos in 1874, but this effort did not materialize until 1881. The rise of this type of associations occurred during the revolutionary period. The year 1978 marked the beginning of profound changes, and by 1980 the Provincial Council of Scientific Societies was legalized as a body to establish relations between scientific societies and the Ministry of Public Health. It is concluded that scientific societies in Cienfuegos emerged in a short period of time in relation to their national counterparts. Several personalities of the province have been members of these associations, which have conducted scientific and social activities of great importance.